Questioning the Truism of Fractured Experience: On the Neo-Orientalist features of Michael Puett's reading of early China. - Rivera Espinoza, Manuel (Polylog, 2023)
The paper begins by revisiting the ongoing debate surrounding Orientalism in early Chinese studies, with a specific focus on the allegations of essentialism and Orientalism leveled against Roger Ames by Michael Puett and Paul Goldin, respectively. Upon a thorough examination of Edward Said's work, it becomes evident that these accusations lack a solid foundation. Furthermore, Puett's interpretation of ancient Chinese texts as illustrating »fractured experience« may itself exhibit neo-Orientalist features. This perspective gains support through the lens of Gayatri Spivak's concept of »epistemic violence« and Edgardo Lander's exploration of the »coloniality of knowledge.« By way of conclusion, the paper proposes that Boaventura de Sousa Santos' ideas may offer a way to escape the Orientalist paradigm and acknowledge non-Western, particularly early Chinese, forms of knowledge and experience.